Relative impact of Fiscal and Monetary Policy on the Growth of Small and Medium Scale Enterprises in Nigeria - Ehikioya, Imoughele Lawrence; Uduh, Dominic Marior; Edeme, Richardson Kojo (Universitas Negeri Malang, 2018)
In order to determine the influence of fiscal and monetary policies on the growth of SMEsin Nigeria, this study employed time series data for the period 1986-2015, adopting the OLS estimation technique. The result suggeststhat fiscal policy is more effective in stimulating the growth performance of Nigeria SMEs comparing to monetary policy. Hence, the suggestion that government should pay more attention to fiscal policy. A combination of both policies is also recommendedfor optimal performance of the SMEs sector in the Nigerian economy.JEL Codes: E63, O11, O23